(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article explores the potential of using English novels in teaching English literature to improve secondary school students’ speaking competencies in Uzbekistan. As speaking is one of the most challenging skills for English as a Foreign Language (EFL) learners, especially in the context of secondary education, the integration of literature, particularly English novels, can provide an effective platform to enhance students’ speaking abilities. This paper examines how the use of novels in the English classroom can increase motivation, foster engagement, and encourage active participation, which are crucial factors for improving speaking competencies. The study provides insights into teaching methodologies, the role of motivation in speaking practices, and how literature can bridge the gap between linguistic competence and communication skills. The findings suggest that a literature-based approach, when combined with interactive and student-centered teaching strategies, can significantly enhance students’ speaking skills.